Impact of decompressive craniectomy on functional outcome of severe acquired brain injuries patients, at discharge from intensive inpatient rehabilitation. Issue 26 (18th December 2022) - Hakiki, Bahia; Liuzzi, Piergiuseppe; Pansini, Gastone; Pancani, Silvia; Romoli, Annamaria; Draghi, Francesca; Orlandini, Simone; Mannini, Andrea; Della Puppa, Alessandro; Macchi, Claudio; Cecchi, Francesca
Abstract: Purpose: Decompressive craniectomy (DC) is a life-saving procedure conducted to treat refractory intracranial hypertension. Although DC reduces mortality of severe Acquired Brain Injury (sABI) survivors, it has been associated with severe long-term disability. This observational study compares functional outcomes at discharge from an Intensive Rehabilitative Unit (IRU) between sABI patients with and without DC. Material and methods: sABI patients undergoing DC before entering the Don Gnocchi Foundation IRU were compared with a group of sABI patients who did not undergo DC (No-DC group), after matching it by age, sex, aetiology, time post-onset, and clinical status. Inclusion criteria were: diagnosis of sABI, age 18+, time from the event <90 days. Results: A total of 87 (DC: 47) patients were included (median age: 60.5 [IQR = 17.47]). The two groups did not differ for admission clinical features except for the tracheostomy presence (more frequent in DC, p  < 0.001). No significant differences were also found at discharge. DC group presented a significantly longer length-of-stay than No-DC group ( p  < 0.001) and a longer time to tracheostomy removal ( p  = 0.036). DC was not found to influence outcomes as consciousness improvement, tracheostomy removal, oral intake and functional independence. Conclusions: sABI patients with DC improved after rehabilitation as much as No-DC patients did but they required a longer stay. Implications for Rehabilitation: Decompressive craniectomy (DC) is practiced during the acute phase after hemorrhagic, ischemic, traumatic severe brain injury as a life-saving procedure to treat refractory intracranial hypertension DC has been associated with follow-up severe long-term disability, but no study yet addressed whether DC may affect intensive rehabilitation outcomes. Undergoing a DC is not a negative prognostic factor for achieving rehabilitation goals after a severe acquired brain injury DC must be taken into account when customizing rehabilitation pathway especially because these patients required a longer time to reach the outcomes.